Angiotensin converting enzyme inhibition in chronic stable angina: effects on myocardial ischaemia and comparison with nifedipine. Issue 1 (January 1994) - Ikram, H.; Low, C. J.; Shirlaw, T. M.; Foy, S. G.; Crozier, I. G.; Richards, A. M.; Khurmi, N. S.; Horsburgh, R. J.
Abstract : OBJECTIVES--To determine the anti-ischaemic effects of a new angiotensin converting enzyme inhibitor, benazepril, compared with nifedipine, alone and in combination, in chronic stable angina caused by coronary artery disease. DESIGN--Placebo controlled, double blind, latin square design. SETTING--Regional cardiology service for a mixed urban and rural population. SUBJECTS--40 patients with stable exertional angina producing at least 1 mm ST segment depression on exercise test with the Bruce protocol. 34 patients completed all four phases of the trial. INTERVENTIONS--Each patient was treated with placebo, benazepril (10 mg twice daily), nifedipine retard (20 mg twice daily), and a combination of benazepril and nifedipine in the same doses, in random order for periods of two weeks. MAIN OUTCOME MEASURES AND RESULTS--Total duration of exercise was not increased by any treatment. Exercise time to the development of 1 mm ST segment depression was not significantly changed with benazepril alone or in combination with nifedipine but was increased with nifedipine from 4.18 (1.8) min to 4.99 (1.6) min (95% confidence interval (95% CI) 0.28 to 1.34; p < 0.05). There was a significant relation between increase in duration of exercise and resting renin concentration (r = 0.498; p < 0.01). Myocardial ischaemia during daily activity, as assessed by ambulatory electrocardiographic monitoring, was reduced by benazepril and by the benazepril and nifedipine combination. This was significant for total ischaemic burden (451(628) min v 231(408) min; 95% CI -398 to -41 min; p < 0.05) and maximal depth of ST segment depression (-2.47(1.2) mm v -2.16 mm; 95% CI 0.04 to 0.57; p < 0.05) for the combination and for maximal ST segment depth for benazepril monotherapy (-2.47 (1.2) mm v -1.96(1.2) mm; 95% CI 0.18 to 0.91; p < 0.05). Benazepril significantly altered the circadian rhythm of cardiac ischaemia, abolishing the peak ischaemic periods at 0700 to 1200 and 1700 to 2300 (p < 0.05). CONCLUSIONS--Benazepril, an angiotensin converting enzyme inhibitor, had a modest anti-ischaemic effect in effort angina, but this effect was not as pronounced as with nifedipine. The anti-ischaemic action was more noticeable in asymptomatic ischaemia during daily activity, whereas nifedipine had little effect on this aspect of myocardial ischaemia. The combination of benazepril and nifedipine reduced ischaemia of daily activity.